Factors associated with knowledge of diabetic retinopathy among adults with diabetes on follow-up care at public hospitals in Addis Ababa, Ethiopia: an institution-based cross-sectional study - Dinsa, Feven; Aga, Fekadu; Gela, Debela (Frontiers in Clinical Diabetes and Healthcare, 2025)
BackgroundDiabetic retinopathy (DR) is the leading cause of vision loss among adults with diabetes aged between 20 to 70 years. Lack of knowledge about Diabetic retinopathy is one of the reasons for treatment delays, which can lead to the development of sight-threatening DR. The aim of this study is to assess knowledge of diabetic retinopathy and associated factor among adults with diabetes mellitus at public hospitals in Addis Ababa, Ethiopia.MethodsAn institution-based cross-sectional study was conducted at five public hospitals in Addis Ababa from 27 February to 27 March 2023.Systematic random sampling was used to select 421 diabetes patients. Data was collected using a pretested interviewer-administered questionnaire using Kobo Collect version 2022.4.4. The data was then exported to SPSS version 27 for cleaning and analysis. Multiple linear regression analysis with a p-value < 0.05 and corresponding 95% confidence interval (CI) was used to identify factors associated with knowledge of DR.ResultsThe respondents’ mean percentage score for DR knowledge was 61.42% ± 28.75%. Longer years lived with diabetes (B = 0.157, p = 0.001) and older age (B = 0.022, p = 0.044) were associated with better DR knowledge score, whereas having no formal education (β = -0.166, p = 0.001) and secondary school education (β = -0.165, p = 0.001) compared to the other groups had lower DR knowledge score.ConclusionLonger years lived with diabetes, older age and higher educational level were factors associated with better knowledge of DR. Therefore, health professionals should target newly diagnosed, relatively younger patients and less educated DM patients when providing diabetes self-management education related to DR.